PENGARUH NILAI TERHADAP SIKAP DAN PERILAKU PENGURANGAN KONSUMSI BERAS PADA IBU RUMAH TANGGA DI WILAYAH PERDESAAN DAN PERKOTAAN - Johan, Irni Rahmayani; Yuliyanti, Tri (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2013)
This study aimed to analyze the values, attitudes, and behavior on rice consumption reduction in rural and urban areas. The research was conducted in the Cikarawang Village and Sempur Village, Bogor. The total samples were 109 housewives who were proportional randomly selected. Data was collected through self-report techniques and analyzed by descriptive and inferential statistics (different test, correlation test, and regression test). The results showed that there were significant differences between values, attitudes (cognitive aspects, affective aspects, and conative aspects), and behavior of rice consumption reduction on consumers who live in rural and urban areas. The correlation test also showed that the values, attitudes, and behaviors of rice consumption reduction were correlated significant . Values and also the attitude of consumers influenced significantly on the behavior of rice consumption reduction.